Development of Propeller Arm Control System for Increased Speed, Maneuverability, and Efficiency of Flying Electric Vehicle - sugeng hadi susilo; Muhammad Ainul Mafazi (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
This paper aimed to design and analyze a propeller arm control system for electric flying vehicles. Since there was an increasing interest in flying vehicle technology, this research focused on developing mechanisms that could improve operational efficiency and stability. The research methods used included literature study, system design, and simulation using Matlab/Simulink software. The results showed that an optimal propeller arm design was able to improve the maneuverability and stability of electric flying vehicles. This research also emphasized on the importance of using advanced navigation and control technologies to ensure safety in operations. In addition, this research identified the need for clearer regulations regarding the use of quadcopters for transportation, as well as the importance of public involvement in the development of this technology. From the analysis, it was recommended to conduct field trials and involve various stakeholders in the development of regulations and flying vehicle technology. This research was expected to make a significant contribution to the development of flying electric vehicles and increase public understanding of this technology